Goethe, J. W. Von. Ifigènia a Tàurida (traducció de Joan Maragall) - Martí Duran (Quaderns)
Goethe, J. W. Von Ifigènia a Tàurida (traducció de Joan Maragall) Barcelona: Comanegra – Institut del Teatre, 2020, 140 p. ISBN 978-84-9803-932-0